Learning Model for Preparing Financial Statements of Village-Owned Enterprises Using the Training, Simulation, and Assistance Model - Andriana, Nina; Priharjanto, Akhmad (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to find an effective learning model for preparing financial statements for Village-Owned Enterprises (VOE). VOE are required to prepare financial statements by the Financial Accounting Standards for Private Entities (SAK-EP) on a semi-annual basis. However, to date, very few VOE can prepare financial statements by the expected accounting standards. This is because most VOE managers do not understand the process of preparing financial statements and do not have an accounting education background. Therefore, an effective learning model for preparing financial statements is needed for VOE managers with non-accounting educational backgrounds. This study uses participatory action research by actively involving VOE managers in learning how to prepare financial statements. After mapping VOE managers and analyzing learning needs, a learning model was developed through three stages: training, simulation, and assistance, referred to as the TSA model. The development of this model refers to Project-Based Learning and Problem-Based Learning, where VOE managers are given the task of preparing financial statements directly using either dummy data or real transaction data. The study was conducted with VOE managers in East Java. After completing the training, VOE managers can prepare financial statements according to standards. Some VOE financial statements have even been audited by a Public Accounting Firm, receiving unqualified and qualified opinions. Therefore, this learning model is an effective accounting education for VOE managers.